A case report with pathological insights into cotyledonoid dissecting leiomyoma: Essential for differentiating this rare benign tumor from cancer - Masoud Edalati; Karam Khouri; Ahmed Lazim; Shuanzeng Wei; Anjali Seth; Daniela Proca (Case Reports in Women's Health)
Cotyledonoid dissecting leiomyoma (CDL), also known as Sternberg tumor, is a rare uterine leiomyoma variant with distinct imaging, gross, and microscopic features that deviate from classic leiomyomas. Despite its benign nature, CDL frequently mimics malignancy on radiologic and clinical evaluations, posing a diagnostic challenge. Understanding its unique characteristics is crucial for correct diagnosis to prevent unnecessary aggressive treatment. This report concerns the case of a 52-year-old postmenopausal woman with abnormal bleeding and an enlarged uterus. Ultrasound revealed a 4.3 × 3.5 × 3.5 cm complex echogenic mass of undetermined etiology in the right adnexa. MRI demonstrated a heterogeneously enhancing, irregular mass between the right ovary and uterine fundus. Given her postmenopausal status, a total hysterectomy with bilateral salpingo-oophorectomy was performed. Gross examination revealed a red, spongy, nodular, and cystic tumor containing gelatinous material. The mass involved the right lateral uterine wall, extending toward the fundus and round ligament, but remained distinct from the ovary and fallopian tube. Microscopically, interlacing smooth muscle fascicles whorled around prominent thick-walled vessels, confirming the diagnosis of CDL—a rare, benign uterine leiomyoma with a unique gross and microscopic appearance. Recognizing CDL is critical for both clinicians and pathologists to avoid misdiagnosing it as malignancy. Increased awareness can prevent unnecessary radical treatment, ensuring appropriate patient management while avoiding potential overtreatment and associated complications.